Citric Acid and Sodium Bicarbonate as an Alternative Carbon Dioxide Source for Mosquito Surveillance - Christine Hong; Victoria J. Brookes; Ruth N. Zadoks; Cameron E. Webb (Insects)
Most mosquito surveillance programs rely on traps baited with carbon dioxide (CO2) to attract host-seeking mosquitoes. The source of CO2, traditionally dry ice or gas cylinders, poses operational challenges, especially in remote locations. CO2 production from citric acid and sodium bicarbonate (NaHCO3) using low-cost intravenous fluid bags (‘acid traps’) was evaluated in laboratory experiments. Field trials then compared the efficacy of these acid traps with dry ice traps. Using a 2 × 2 Latin square style design, trapping locations were established at two sites in Sydney, New South Wales, Australia (one urban and another peri-urban), to assess trap performance in diverse environments. The laboratory results showed CO2 production of sufficient amount and duration for overnight mosquito capture. Whilst field experiments showed that dry ice traps captured more mosquitoes (up to 59%) than acid traps, numbers were similar in the urban environment. At both sites, species composition was similar, with Culex quinquefasciatus, Aedes notoscriptus, and Aedes vigilax predominantly collected, and these are known species of pest and public health concern. Further modifications to the acid traps could further improve CO2 output and trap efficiency.